Cohens Psychologie Annäherungen an ein unvollendetes Projekt - Wiese, Christian; Dober, Hans Martin; Dober, Hans Martin (Mohr Siebeck, 2024)
Cohens Psychology. Approaches to an Unfinished Project.
PublicationDate: 20250219
Keywords: Judentum -- Kultur -- Religion -- Vernunft -- Seele -- Religionsphilosophie -- Neuzeit -- Array